2015
DOI: 10.1073/pnas.1504552112
|View full text |Cite
|
Sign up to set email alerts
|

Tenebrionid secretions and a fungal benzoquinone oxidoreductase form competing components of an arms race between a host and pathogen

Abstract: Entomopathogenic fungi and their insect hosts represent a model system for examining invertebrate-pathogen coevolutionary selection processes. Here we report the characterization of competing components of an arms race consisting of insect protective antimicrobial compounds and evolving fungal mechanisms of detoxification. The insect pathogenic fungus Beauveria bassiana has a remarkably wide host range; however, some insects are resistant to fungal infection. Among resistant insects is the tenebrionid beetle T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
123
3
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 80 publications
1
123
3
4
Order By: Relevance
“…are known to be difficult to kill with entomopathogenic fungi in laboratory bioassays (Rice & Cogburn, 1999;Padin et al, 2002;Akbar et al, 2004;Wakefield et al, 2005;Wakefield, 2006;Michalaki et al, 2006Michalaki et al, , 2007. This was recently shown to be due in part to the production of cuticular defensive secretions that inhibit growth of B. bassiana and other microbes (Pedrini et al, 2015). also found differences in the number of fungal isolates with respect to the location where they had been sampled and a similar variation was noted in our study, especially in sites sampled in the city of Adana, which contributed most of the observed variation.…”
Section: Discussionmentioning
confidence: 99%
“…are known to be difficult to kill with entomopathogenic fungi in laboratory bioassays (Rice & Cogburn, 1999;Padin et al, 2002;Akbar et al, 2004;Wakefield et al, 2005;Wakefield, 2006;Michalaki et al, 2006Michalaki et al, , 2007. This was recently shown to be due in part to the production of cuticular defensive secretions that inhibit growth of B. bassiana and other microbes (Pedrini et al, 2015). also found differences in the number of fungal isolates with respect to the location where they had been sampled and a similar variation was noted in our study, especially in sites sampled in the city of Adana, which contributed most of the observed variation.…”
Section: Discussionmentioning
confidence: 99%
“…Entomologists examine these host-pathogen interactions not only to obtain better insights on the forces driving natural selection, but also to devise novel environmentally safe alternatives to control insect population while reducing our nation's dependence on conventional agricultural chemicals. In PNAS, the multidisciplinary and multinational team of Pedrini et al unravel a mystery in the insect-fungus arms race (2).…”
mentioning
confidence: 99%
“…These quinones are very toxic (7) and keep fungus at bay. Intrigued that degradation of quinone derivatives by other fungi is very common, Pedrini et al (2) asked the question: Why doesn't B. bassiana use its biochemical machinery to degrade/ detoxify quinones and get one step ahead in this race? Surprisingly, the authors found that the fungus is working on it.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite B. bassiana being able to infect a broad range of arthropods, there are reports of insects that are refractory to infection by B. bassiana. For instance, the red flour beetle Tribolium castaneum is not susceptible to infection by B. bassiana, and this is attributed to its ability to produce quinone-containing cuticular secretions that act as antimicrobial defence compounds (Pedrini et al, 2015;Yezerski et al, 2007). Nevertheless, as explained above, EPF have a lower killing capacity than insecticides, which allows mosquitoes to reproduce before dying.…”
Section: The Risk Of Resistancementioning
confidence: 99%